TEACHING STRATEGIES IN UNDERGRADUATION COURSES OF A BRAZILIAN PUBLIC UNIVERSITY - Leal de Souza Oliva, Valeria Nobre [UNESP]; Spazziani, Maria de Lourdes [UNESP]; Barreto de Oliveira, Jose Bras [UNESP]; Colvara, Laurence Duarte [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education A& Development, 2016)
This article aimed to identify the teaching strategies used by Professor-Team segment of undergraduate courses at a Brazilian Public University and typifies them according to the teaching methods used in: individual, socialized and socio-individualized. In addition, it tried to identify the resources most used by teachers working in different areas of knowledge. The study was conducted with the identification and analysis of teaching strategies and resources present in abstracts published in a collection of Teaching Methodologies (http://www.unesp.br/portal#!/prograd/e-livros-prograd). The texts were organized and classified in three areas of knowledge: Humanity, Biological and Exact. Within each area were identified and analyzed the methodological aspects in practical educational proposal or developed. Were evaluated 25 abstracts of Humanity, 12 of Exact and 23 of Biological areas, in a total of 60 abstracts. Both in Biological Sciences as Humanities areas the professors preferred to use socialized or socio-individualized methods to teach the subjects contents and used the method individualized but with a lower prevalence. In the Exact Area the socio-individualized were the most frequent method reported (75%), followed by individual teaching practice (25%), without occurrence of using socialized method. In Humanities, the teaching strategies with the highest prevalence were reading texts, study of the environment, play activities, awareness and discussions with significant occurrence of Project Based Learning methodology (PBL). Prior reading, visits, case studies, reflective journals, portfolios and PBL have been widely used in Life Sciences. In the field of Exact Sciences the most common strategies were the production of objects, drawings and PBL. The information and communication technologies (ICT) were predominantly used in the Exact Area, restricted to the use of software and digital production figures. In Biological Area were used videos, virtual learning environment (VLE), social media and image scanning software. The use of ICT in the humanities was less frequent than in other areas, restricting the use of social networking and the VLE. The interdisciplinary approach was used most frequently by teachers of Biological courses, followed by those in the Humanities area. There were no reported interdisciplinary experiences in the Exact area. It can be concluded that the reports presented to the composition of this collection demonstrate the use of various teaching methodologies and strategies, with a prevalence of some types within the same field of knowledge, reflecting the appreciation of social interaction and socio-individualized practices among professors who teach contents of Biological Science and Humanity. In the Exact Sciences there was no occurrence of socialized methods.
Keywords: Innovation; teaching methodology; undergraduate